Global proteomics reveals pathways of mesenchymal stem cells altered by Mycobacterium tuberculosis - Simran Kaur; Nupur Angrish; Madavan Vasudevan; Garima Khare (Scientific Reports)
Abstract Mycobacterium tuberculosis (M. tb) has a remarkable ability to persist inside host cells. Several studies showed that M. tb infects and survives inside bone marrow mesenchymal stem cells (BM-MSCs) escaping the host immune system. Here, we have identified various cellular pathways that are modulated in human BM-MSCs upon infection with virulent M. tb and the proteomic profile of these cells varies from that of avirulent M. tb infected cells. We found that virulent M. tb infection reshapes host pathways such as stem cell differentiation, alternative splicing, cytokine production, mitochondrial function etc., which might be modulated by M. tb to persist inside this unconventional niche of human BM-MSCs. Additionally, we observed that virulent M. tb infection suppresses various cellular processes. This study uncovers the differences in the host proteomic profiles resulting from the virulent versus avirulent M. tb infection that can pave the way to identify host-directed therapeutic targets for the treatment of tuberculosis.